2020
DOI: 10.1088/1757-899x/928/2/022018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Water Surface Change of Haditha Dam’s Lake Using Satellite Data Technique

Abstract: Water bodies in Iraq and other countries are considered the essential key for human life as they play a large and influential role in the country’s economy. Thus, the strategic plans of water management must be developed according to the need for future requirements. The current study aims to monitor the change in the water surface area of Haditha Dam Lake by calculating the surface area of the lake over a sequential time (1985-2019). GIS and Satellite imagery techniques were used to achieve the goal of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…They concluded that understanding the effects of running hydropower plant turbines on the dam body is one of the major safety concerns for the earthfill dam, besides other safety concerns such as karstification. Sissakian et al (2018) described the general geology of Haditha Dam, and Hason et al (2020) conducted change detections study over the impounded area of Haditha Dam reservoir for many years, see Figure 1. The main aim of the current study is to elucidate and discuss the influence of the karstified rocks at the dam site and reservoir on the design and especially the length of the dam and the need for side extensions.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They concluded that understanding the effects of running hydropower plant turbines on the dam body is one of the major safety concerns for the earthfill dam, besides other safety concerns such as karstification. Sissakian et al (2018) described the general geology of Haditha Dam, and Hason et al (2020) conducted change detections study over the impounded area of Haditha Dam reservoir for many years, see Figure 1. The main aim of the current study is to elucidate and discuss the influence of the karstified rocks at the dam site and reservoir on the design and especially the length of the dam and the need for side extensions.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Therefore, deformation measurements and analysis require high-precision surveying equipment and analysis of the data to identify and avoid hazards. In addition to studying, the sediments collected at upstream of the barrage over time and understanding the eff ect of sediments on the effi ciency of the barrage gates [Abedalrahman and Mnaty, 2021;Hason et al, 2020].…”
Section: Introductionmentioning
confidence: 99%